Long-term outcomes of second-line antiretroviral treatment in an adult and adolescent cohort in Myanmar. Issue 1 (1st January 2017) - Kyaw, Nang Thu Thu; Kumar, Ajay M. V.; Oo, Myo Minn; Oo, Htun Nyunt; Kyaw, Khine Wut Yee; Thiha, Soe; Aung, Thet Ko; Win, Than; Mon, Yin Yin; Harries, Anthony D.
ABSTRACT: Background : Myanmar has a high burden of Human Immunodeficiency Virus (HIV) and second-line antiretroviral treatment (ART) has been available since 2008 in the public health sector. However, there have been no published data about the outcomes of such patients until now. Objective : To assess the treatment and programmatic outcomes and factors associated with unfavorable outcomes (treatment failure, death and loss to follow-up from care) among people living with HIV (aged ≥ 10 years) receiving protease inhibitor-based second-line ART under the Integrated HIV Care Program in Myanmar between October 2008 and June 2015. Design : Retrospective cohort study using routinely collected program data. Results : Of 824 adults and adolescents on second-line ART, 52 patients received viral load testing and 19 patients were diagnosed with virological failure. However, their treatment was not modified. At the end of a total follow-up duration of 7 years, 88 (11%) patients died, 35 (4%) were lost to follow-up, 21 (2%) were transferred out to other health facilities and 680 (83%) were still under care. The incidence rate of unfavorable outcomes was 7.9 patients per 100 person years follow-up. Patients with a history of injecting drug use, with a history of lost to follow-up, with a higher baseline viral load and who had received didanosine and abacavir had a higher risk of unfavorable outcomes. Patients with higher baseline C4 counts, those having taken first-line ART at a private clinic, receiving ART at decentralized sites and taking zidovudine and lamivudine had a lower risk of unfavorable outcomes. Conclusions : Long-term outcomes of patients on second-line ART were relatively good in this cohort. Virological failure was relatively low, possibly because of lack of viral load testing. No patient who failed on second-line ART was switched to third-line treatment. The National HIV/AIDS Program should consider making routine viral load monitoring and third-line ART drugs available after a careful cost–benefit analysis.